A Qualitative Study on Factors Associated with Low Academic Performance among Medical Students (Indian Journal of Public Health Research & Development, 2023)
Introduction: To ensure optimal quality of health care for the community, it is important to produce an efficientprimary care provider. In order to attain this quality we must ensure that all students achieve the requiredstandards. In spite of pre-set prescribed standards, the academic performance varies among medical students.Objectives: 1. Describe the factors affecting the learning of medical students. 2. Explore the possible solutions toimprove their academic performance.Materials and Methods: A total of 18 students and 12 faculties participated in the study. Among them, five FocusGroup Discussions (FGD) were carried out (three FGDs with students and two FGDs with faculties). The discussionwas guided by a facilitator and audio-recorded. Information from the audio was transcribed.Results: Factors affecting learning include content of the class, class schedule, attention span, assessment pattern,audio-visual aids, level of integration of classes, ability of the teacher and teaching learning methods used.Solutions include field visits, hands-on training, appropriate use of audio-visual aids, integration of classes, activeparticipation in research, communication with peers, strict maintenance of attendance and motivation of thestudents, etc,.Conclusion: Addressing all the factors hindering the learning process by incorporating solutions suggested byfaculties and students may help the learners to improve their academic performance. It is important to teach thetopics with its practical application with an appropriate assessment pattern.
Keywords: Academic performance, Medical students, Focus Group Discussion, Assessment, Communication, Integration.